Pemanfaatan kotoran ternak dengan dosis yang berbeda terhadap pertumbuhan dan biomassa cacing sutra (Tubifex sp.) - Wenda, Detiben; Pangkey, Henneke; Mokolensang, Jeffrie F. F. (e-Journal BUDIDAYA PERAIRAN, 2018)
The purpose of this study was to analyze the use of cattle dung on the growth and biomass of silk worms. The experiment was conducted at Freshwater Aquaculture Center (BPBAT) Tatelu, Tatelu Village, Dimembe Subdistrict, North Minahasa Regency, North Sulawesi Province, about 35 km from Manado city. The media used was pig manure, chicken manure, cow dung, and fine mud added with EM4. The method used was complete randomized design (RAL) with 4 treatments including A. 500 g of pig manure, 500 g of chicken manure 500 g of cow dung, and 500 g of fine mud; B. 600 g of pig manure, 400 g of chicken manure 500 g of cow dung, 500 g of fine mud; C. 700 g of pig manure, 300 g of chicken manure, 500 g of cow dung, 500 g of fine mud; and K (control) was 2000 g of fine mudinand, each with 3 replications. Water quality parameters measured during the study were temperature, pH, DO, nitrate and nitrite. The results showed that there was a very significant effect on growth but not for the value of silk worm biomass. The highest growth was found in treatment A that was 38 g, while for the highest biomass also in treatment A namely 1.5 g / cm3. Water quality parameters during the study were 24.3-25.4Â° C, pH 7,1-7,3; DO 2.7-5,7 ppm; nitrate 1.1-1.4 ppm; nitrite 0.011-0.201 ppm.Keywords: Â Cattle dung, growth, biomass, Tubifex sp., aquaculture